Dual Roles of microRNA-122 in Hepatocellular Carcinoma and Breast Cancer Progression and Metastasis: A Comprehensive Review - Essam Al Ageeli (Current Issues in Molecular Biology)
microRNA-122 (miR-122) plays crucial yet contrasting roles in hepatocellular carcinoma (HCC) and breast cancer (BC), two prevalent and aggressive malignancies. This review synthesizes current research on miR-122’s functions in these cancers, focusing on its potential as a diagnostic, prognostic, and therapeutic target. A comprehensive literature search was conducted using PubMed, Web of Science, and Scopus databases. In HCC, miR-122 is downregulated in most cases, suppressing oncogenic pathways and reducing tumor growth and metastasis. Restoring miR-122 levels has shown promising therapeutic potential, increasing sensitivity to treatments like sorafenib. In contrast, in BC, miR-122 plays a pro-metastatic role, especially in triple-negative breast cancer (TNBC) and metastatic lesions. miR-122′s ability to influence key pathways, such as the Wnt/β-catenin and NF-κB pathways in HCC, and its role in enhancing the Warburg effect in BC underline its significance in cancer biology. miR-122, a key factor in breast cancer radioresistance, suppresses tumors in radiosensitive cells. Inhibiting miR-122 could reverse resistance and potentially overcome radiotherapy resistance. Given its context-dependent functions, miR-122 could serve as a potential therapeutic target, where restoring or inhibiting its expression may help in treating HCC and BC, respectively. The dual roles of miR-122 underscore its significance in cancer biology and its potential in precision medicine.